Identification of triazinoindol-benzimidazolones as nanomolar inhibitors of the Mycobacterium tuberculosis enzyme TDP-6-deoxy-D-xylo-4-hexopyranosid-4-ulose 3,5-epimerase (RmlC) - Sivendran, Sharmila (2009)
High-throughput screening of 201,368 compounds revealed that 1-(3-(5-ethyl-5H-[1,2,4]triazino[5,6-b]indol-3-ylthio)propyl)-1H-benzo[d]imidazol-2(3H)-one (SID 7975595) inhibited RmlC a TB cell wall biosynthetic enzyme. SID 7975595 acts as a competitive inhibitor of the enzyme’s substrate and inhibits RmlC as a fast-on rate, fully reversible inhibitor. An analog of SID 7975595 had a K(i) of 62 nM. Computer modeling showed that the binding of the tethered two-ringed system into the active site occurred at the thymidine binding region for one ring system and the sugar region for the other ring system.